ANALISIS SELEKSI JABATAN PIMPINAN TINGGI PRATAMA DI LINGKUNGAN PEMERINTAH PROVINSI RIAU TAHUN 2015 - Monalisa, Monalisa; Dinata, Dody Saputra (UIR PRESS, 2017)
To be able to perform tasks of public services, administration tasks, and task specific development, Employees ASN must have a profession and management of ASNs is based on the System of Merit or a comparison between the qualifications, competence, and performance required by the office of the qualifications, competence, and performance owned by candidates in the recruitment, appointment, placement, and promotion to the position held in an open and competitive, in line with good governance. Formulation of the problem in this research is how the Selection Process High Primary Leadership Position in the Provincial Government of Riau in 2015 and what the Obstacles and Supporting Positions Selection Process Leader in High-Primary within the Government of Riau Province in 2015. The purpose of the study was to analyze the implementation of the Job Selection High Primary leaders in the Government of Riau Province in 2015 as well as to analyze the factors inhibiting and supporters. The study was conducted in Riau Province Government. Qualitative descriptive research with a number of respondents amounted to 8 people sampled in the study. The nature of the research is the explanation (explanatory). The process of structural positions openly charging for high office environment pratama Riau provincial government began to hold the announcement. Further to the implementation procedure, starting with the formation of the selection committee by the Trustees Personnel Officer. Carry out the selection by the selection committee is assisted by a team of independent assessors competencies. The selection is divided into the administration and the selection of competence.The limiting factor in the selection process pratama high leadership positions within the Government of Riau Province including the lack of planning guidelines in the implementation of selection where in the preparation of the schedule for the final interview held at night that many complained of by the participant selection. While the supporting factors in the selection process of leadership positions higher pratama environment of the Riau provincial government is the rule of law that can guarantee the implementation process of selection goes well and the support and the serious attention of the Governor of Riau to the implementation of this selection in accordance with the expectations of all parties.